LESSOR’S NOTICE OF TERMINATION OF RESIDENTIAL LEASE IN CZECH LAW - Hadamcik, Lukas (Zbornik radova Pravnog fakulteta u Nišu, 2020)
Czech private law underwent a major change in 2014. That year the new Civil Code came into force. The changes also influenced the regulation of residential leasing. Renting a flat or house is a very common mean of satisfying the need for housing in the Czech Republic. In 2011, one quarter of all flats in the Czech Republic were rented. A lessee is considered to be the weaker party in a lease relationship. For this reason, there is strong legal regulation. One way to protect lessees is to limit the lessor’s right to give notice. The aim of this contribution is to present Czech regulation of the termination of residential leases, mainly the circumstances and conditions under which the lessor has the right to give notice.